THE NUTRIENTS BALANCE OF CROP ROTATION AS AN INDICATOR OF SUSTAINABLE FARMING ON ARABLE LAND - Eva Hanáčková; MILAN MACÁK; Eva CANDRÁKOVÁ (Journal of Central European Agriculture, 2009)
The nutrient balance of five crop rotation systems under conventional and minimal tillage with interaction of different fertilization treatments was investigated at the experimental station of Slovak Agricultural University in Nitra Dolná Malanta, during 2004-2005. The five-field crop rotation of maize (Zea mays L.) - winter wheat (Triticum aestivum L.) - spring barley (Hordeum vulgare L.) underseeded with red clover - red clover (Trifolium pratense) - common pea (Pisum sativum L.) and mustard as catch crop was used. The most serious deficit of nitrogen (- 62.2 kg.ha-1.yr-1), phosphorus (- 24.0 kg.ha-1.yr-1) and potassium (- 89.2 kg.ha-1.yr-1) was on control treatments. Deficit of nitrogen was also found-out in treatments with mineral fertilizers application. However higher deficit of nitrogen (- 25.4 kg.ha-1.yr- 1) was registered under conventional tillage. In treatment fertilized with mineral fertilizers together with by - product of pre - crop incorporation into soil (PZ), small balance surplus of nitrogen (8 kg.ha-1.yr-1 - B1, 11.5 kg. ha-1.yr-1 - B2, respectively) was calculated. The positive balance of phosphorus achieved in treatments with into soil incorporated by - products of pre - crops (in both systems of soil cultivation amounting value of 3.9 kg.ha-1.yr-1) can contribute to good supply of phosphorous in soil. The negative balance of potassium fluctuating from - 89.2 kg.ha-1.yr-1 (control treatment) to - 22 kg.ha-1.yr-1 (PZ) is acceptable owing to high content of available potassium in soil of experimental stand.